Analisis Kadar Zat Besi dan Daya Terima Dimsum Ikan Tongkol (Euthynnus affinis) dengan Penambahan Tepung Kacang Kedelai (Glycine max) untuk Pencegahan Anemia: Analysis of Iron Content and Acceptability of Tuna (Euthynnus affinis) Dim Sum Enriched with Soybean Flour (Glycine max) for Anemia Prevention - Devi Ajeng Nur Islami; Farida Wahyu Ningtyias; Abdul Azis Akbar (Universitas Airlangga, 2026)
Background: One of the nutritional problems often experienced by teenagers in Indonesia is anemia. The prevalence of anemia in teenagers aged 15-24 according to the Indonesian Ministry of Health in 2018 was 32%. This is due to the lack of iron absorption in the body. Processing tuna dimsum with the addition of soy flour is expected to be an alternative snack to prevent anemia. Objective: Analyzing the iron content and acceptability of cod dimsum (Euthnmus affinis) with the addition of soybean flour (Glycine max) for the prevention of anemia. Methods: This study used a quasi-experimental design with a posttest-only control group design carried out with 4 treatments and 3 repetitions. The comparison formula of tuna fish, soybean flour studied was X₀= (100%: 0%), X₁ (90%: 10%), X₂ (85%: 15%), X₃ (80%: 20%). The iron content of dimsum was measured using the Atomic Absorption Spectrophotometer (AAS) method. Acceptability testing used the Hedonic Scale Test, with 25 semi-trained panelists. Iron content data were analyzed using the One Way Anova test, while acceptability test data were analyzed using the Friedman test. Results The results of the acceptability test showed significant differences in color and texture parameters, but not in taste and aroma parameters. The results showed an increase in iron levels along with the addition of soy flour. Based on the statistical analysis of One Way Anova, there was a significant difference in iron levels (p value <0.05). The best formula based on MPE is X₁ with an iron content of 0.72 mg (35 grams/piece). The recommended consumption of dimsum as a snack is 4 pieces/day for teenagers aged 13-18 years. Conclusion: The addition of soybean flour to cob dim sum has a significant effect on the iron content, color, and texture. However, it does not affect the taste and aroma.